Run-Length Coding Algorithm Based Satellite Image Compression - Lakshmi Lakshmi; E.A. Mary Anita (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2017)
Image compression is an application based on data compression of the digital images. Its main objective is to reduce the redundancy of the image data for storing and transmitting data in an easy way. In this system we are proposing a compression technique based on the Run-length coding algorithm based on satellite image compression. The Run-length coding algorithm is a part of the Lossless compression algorithm. The performance evolution can be done by calculating the PSNR values of the compressed images.